2020
DOI: 10.1007/698_2019_386
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary Archives Reveal the Concealed History of Micropollutant Contamination in the Seine River Basin

Abstract: Sedimentary archives provide long-term records of particulate-bound pollutants (e.g. trace metal elements, PAHs). We present the results obtained on a set of selected cores from alluvial deposits within the Seine River basin, integrating the entire area's land uses upstream of the core location, collected upstream and downstream of Paris megacity and in the estuary. Some of these cores go back to the 1910s. These records are complemented by in-depth studies of the related pollution emissions, their regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…The PIREN-Seine programme focuses mainly on the Seine River basin upstream of its estuary, the latter also being studied by the long-term programme, Seine-Aval, which started in 1995 [36]. The main experimental sites studied within the Seine River basin and the coring sites presented in Ayrault et al [26] are shown in Fig. 1 and will be discussed in further detail in the following chapters.…”
Section: The Hydrological Features Of the Seine River Basinmentioning
confidence: 99%
See 2 more Smart Citations
“…The PIREN-Seine programme focuses mainly on the Seine River basin upstream of its estuary, the latter also being studied by the long-term programme, Seine-Aval, which started in 1995 [36]. The main experimental sites studied within the Seine River basin and the coring sites presented in Ayrault et al [26] are shown in Fig. 1 and will be discussed in further detail in the following chapters.…”
Section: The Hydrological Features Of the Seine River Basinmentioning
confidence: 99%
“…Deindustrialization and industrial wastewater treatment promoted by the Seine-Normandy Basin Agency (AESN) led to an improvement in the quality of the Seine River's water. Until the late 1980s, the level of toxic substances in the river, the fluxes released by both the city and its industries, and their effects on receiving waters were largely ignored by French scientists and authorities [26,42,47].…”
Section: Industries and Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is achieved by means of (1) historical research (e.g. [6]), (2) retrospective modelling based on data on past pressures established by scientists and on pressure-state models and (3) analysis of sedimentary archives [7].…”
Section: Figmentioning
confidence: 99%
“…Only few flux-flow comparisons have been made for the Seine basin, providing precious information on the socio-hydrosystem metabolism and its evolution over time. The 'leakage rates' of the basin have been assessed for heavy metals, Cd, Cu, Hg, Pb and Zn, which ranged in the 2000s from 0.1 to 10%, depending on the metals [14] (see also [7] on sedimentary archives).…”
Section: Territorial Metabolism: Comparing River Fluxes and Materials mentioning
confidence: 99%